Curbing Islamophobia: The Role of Liquid Organizations in Preserving American Muslim Identity and Islamic Civilizational Values - Supian Sodik (TSAQAFAH, 2025)
Islamophobia remains a significant challenge in American society, influencing public perceptions and shaping the lived experiences of Muslim communities. In response, the Council on American-Islamic Relations (CAIR) has emerged as a key organization in strengthening American Muslim identity. This study examines CAIR’s organizational role in countering Islamophobia by fostering resilience, increasing community engagement, and enhancing cultural representation. Using a qualitative approach, it explores how liquid organizations navigate structural barriers and social prejudice while promoting inclusivity and civic participation. The findings indicate that such organizations reinforce identity formation by providing safe spaces for dialogue, utilizing digital platforms for advocacy, and facilitating interfaith engagement. Their flexible organizational structures enable rapid adaptation to emerging challenges, making them effective in mobilizing support and shaping narratives that challenge negative stereotypes. By amplifying Muslim voices and building solidarity, liquid organizations contribute to a more pluralistic and inclusive society. This study highlights their transformative potential in redefining American Muslim identity amid ongoing sociopolitical tensions. Ultimately, recognizing and supporting these organizations represents an important step toward reducing Islamophobia.